Beyond ethics: The transformational power of overlapping motivations in implementing strategic sustainability actions. (18th October 2021) - Bonilla‐Priego, Maria Jesus; Nájera‐Sánchez, Juan‐José; Font, Xavier
Abstract: We develop a methodology to identify patterns between sustainability motivations, actions and engagement. We apply this methodology to analyse a 3 1/2‐year intervention that yielded 151 sustainability actions undertaken by 46 outbound tour operators. We find three aspects that can be explained by the tour operators' motivations to act sustainably, namely, a connection between: (i) the actions taken in the context of the organisation's business model, (ii) the intensity of the approach, measured by the resources invested in it and the operator's commitment level and (iii) the evolution of the response. These patterns demonstrate how ethical motivations are common and a precondition to acting sustainably, but, in themselves, these motivations are not sufficient to integrate sustainability practices into the core business or to maintain commitment over time. It is the combination of a high ethical commitment with clear strategic intent, materialised in commercial and operational motivations, that increases the connectedness, and intensity, of sustainability actions amongst ethically committed firms.